2000
DOI: 10.1667/0033-7587(2000)154[0477:piifei]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Particle Irradiation Induces FGF2 Expression in Normal Human Lens Cells

Abstract: Particle Irradiation Induces FGF2 Expression in Normal Human Lens Cells. Particle radiations, including both proton and helium-ion beams, have been used to successfully treat choroidal melanoma, but with the complication of radiation-induced cataract. We have investigated a role for radiation-induced changes in the expression of basic fibroblast growth factor (FGF2) gene expression as part of the mechanism(s) underlying lens cell injury associated with cataract. Normal human lens epithelial (HLE) cells were cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…This was unexpected as 0.5 Gy is a dose that inactivates clonogenic potential of 31% of clonogenic HLEC1 [11], although expression changes at later time points need to be tested. The time and dose point of 3 h after 4 Gy was based on reports by Chang et al who used pathway arrays and showed upregulation of FGF2 and CDKN1A and downregulation of cyclin G1, CDC2, CHK2, TIMP1, MMP-2, -3 and -9 at 3 h after irradiation of human LECs with 4 Gy of X-rays, protons, helium or iron ions [4244]. Of these, upregulation of only FGF2 was observed in HLEC1 at p <0.05 and FDR <0.1, although upregulation of CDKN1B (p27 Kip1 ), downregulation of CCNA2 (cyclin A2) and CCNB1 (cyclin B1) were observed instead (S3 and S4 Tables).…”
Section: Discussionmentioning
confidence: 99%
“…This was unexpected as 0.5 Gy is a dose that inactivates clonogenic potential of 31% of clonogenic HLEC1 [11], although expression changes at later time points need to be tested. The time and dose point of 3 h after 4 Gy was based on reports by Chang et al who used pathway arrays and showed upregulation of FGF2 and CDKN1A and downregulation of cyclin G1, CDC2, CHK2, TIMP1, MMP-2, -3 and -9 at 3 h after irradiation of human LECs with 4 Gy of X-rays, protons, helium or iron ions [4244]. Of these, upregulation of only FGF2 was observed in HLEC1 at p <0.05 and FDR <0.1, although upregulation of CDKN1B (p27 Kip1 ), downregulation of CCNA2 (cyclin A2) and CCNB1 (cyclin B1) were observed instead (S3 and S4 Tables).…”
Section: Discussionmentioning
confidence: 99%
“…28,36 In vivo, FGF2 released into the coronary circulation after vascular injury promotes human vascular smooth muscle cell proliferation. 4 Similar to mechanical damage, cell membrane injury from ionizing radiation induces FGF2 expression and release in endothelial and epithelial cells in vitro 5,23,24 and in vivo. 41 FGF2 enhances endothelial, epithelial, and hematopoetic cell survival after ionizing radiation, 18,19,22,23 and FGF2 release is critical to radiation damage repair.…”
Section: Discussionmentioning
confidence: 99%
“…LBNL investigated a role for radiation-induced changes in the expression of basic Fibroblast Growth Factor ( FGF-2 ) gene expression as part of the mechanism(s) underlying lens cell injury associated with cataract (Chang et al 2000). HLE cells were exposed to a single dose of protons (LET = 1.18 keV μm −1 ) or helium ions (LET = 7.2 keV μm −1 ) at the 88-inch cyclotron at LBNL.…”
Section: In Vitro Molecular Responses Of Hle During Post-exposure Latmentioning
confidence: 99%